MENOPAUSE AND SLEEP DISTURBANCES - I. M. Madayeva (Scientific Сentre for Family Health and Human Reproduction Problems, 2012)
The article contains the review of literature data of domestic and foreign researchers concerning the issues of climacteric period, in women.